A Overview of the 2023 FKIK UKRIDA Study Program Students Breakfast Menu Variations - Kurniawan, Inge; Winaktu, Gracia JMT; Susanto, Lucianana Budi; Hartanto, Hartanto (Jurnal MedScientiae, 2024)
The Balanced Nutrition Guidelines (PGS) presented by the Indonesian Ministry of Health in 2014 have a message, one of which is to get used to breakfast. Breakfast is an eating and drinking activity carried out between waking up and 9 am with the aim of meeting daily nutritional needs (15-30%). This research aims to get an overview of the variations in the breakfast menu of FKIK UKRIDA students. This research used a cross sectional descriptive design, taking subjects using purposive sampling. Data collection was carried out in October 2023. The research subjects consisted of 45 students who met the inclusion and exclusion criteria. The inclusion criteria are the 2020-2021 class who are aged 19-25 years and who eat breakfast. The results of this study showed that most of the subjects were female, namely 32 people (71.1%). Most of the subjects did not live with their parents/boarding house 27 (60%) with monthly pocket money mostly Rp. 1,000,000 – Rp. 2,500,000, namely 23 people (51.1%). Most of the subjects had normal weight nutritional status, namely 26 people (40%). The description of the subject's breakfast menu is quite varied, namely bread 14 (31.1%), fried chicken rice 11 (24.4%), and others 20 (42.1%), drinks namely water 22 (48.9%) , water and milk 5 (11.1%), and others 18 (37.8%).